Corporate Social Responsibility: toward a generic implementation framework for firms - Cruz, C. L. (EURAM Doctoral Colloquium, 2020)
Fostering Corporate Social Responsibility (CSR) is unarguably a must have competence for any manager in contemporary business environment. A fast-growing sustainability awareness of the consumer society is every day scrutinizing and demanding more from company leaders to work for a sustainable world, now and for future generations. Leading a firm with purpose brings inspiration to stakeholders, creates future goodwill and provides differentiation versus competition, nonetheless what really matters are the actions that materialize that purpose. This research proposal aims to explain how a future thesis will contribute to build a CSR generic implementation framework for firms. The research method will draw on a holistic multiple-case study approach, with primary data collected from interviews to leaders and top management teams and applying thematic analysis as data analysis methodology. Applying the theory of planned behavior and intention-behavior gap model to organizations’ leader motivations towards CSR, the researcher expects to explore key behaviors, drivers and inhibitors of CSR strategies into action. Thus, CSR can be embedded in all company decisions, measured with concrete actions, and valued by all stakeholders as part of the vison and strategy of managing with purpose.